NUTRITION INTAKE AND KNOWLEDGE, BODY IMAGE PERCEPTION, EATING DISORDER RISK AND INTENTION OF BEHAVIOR CHANGE OF FEMALE BRAZILIAN ATHLETES (Fiep Bulletin - online, 2014)
This cross-sectional study aimed to evaluate the nutritional intake, body image, risk of eating disorders and intention of behavior change of female brazilian athletes. sixty-nine athletes from different sports (teAm: volleyball, handball, indoor soccer and basketball n=46; com: judo, karate n=9; rG: rhythm gymnast n=14) had their anthropometric and body composition evaluated, answered questions on nutritional knowledge and beliefs, body image, eating disorders, and intention of changing eating behavior, and reported their 24h food intake. Athletes presented signifi cant difference in age (teAm: 17.3y±1.46; com: 20.6y±5.66; Gr: 16.0y±4.64; p=0.03). mean body mass index (bmi 19.91kg/m2±2.88) and fat percentage (%f 18.8±3.82) of rG were lower than teAm (23.26±2.65kg/m2, p=0.01; %f=23.98±5.31, p=0.03) and com (22.96±2.75kg/m2, p=0.021; %G=25.03±3.88, p=0.015). rG had de lowest mean energy intake (1533kcal±533). no differences in macronutrient intake were observed between groups. mean carbohydrate intake was low (
Keywords: nutrition; body image; team sport; combat sport; rhythm gymnastic